Empagliflozin: an exciting prospect in the treatment of diabetes - George, Melvin; Srinivas, Karthik; Sriram, Damal Kandadai (International Journal of Basic & Clinical Pharmacology, 2017)
Type 2 diabetes mellitus (T2DM) continues to be a chronic and disabling disease that is associated with high mortality and morbidity. The epidemic burden of diabetes mellitus has increased in developing countries and Asia is considered as the “diabetic epicentre”. Type 2 diabetes (T2DM), is characterised by reduced secretion of insulin from pancreatic beta cells independently or associated with reduced response of peripheral tissues to circulating insulin. A proper glycaemic control is essential to delay the micro and macrovascular complications of T2DM. Standard anti-diabetic agents including insulin happen to induce minor to major adverse outcomes in certain populations over prolonged period of administration. Hence there has been a compelling need to develop newer and novel approach to treatment of T2DM. Sodium-glucose co-transporter 2 (SGLT-2) inhibitors are a novel category of drugs that happen to reduce glycaemic overload by inducing glycosuria. The safety, efficacy and tolerability profile of these drugs were studied separately under various trials and was approved for use in August 2014 by US-FDA. This review is an attempt to describe the history of SGLT-2 inhibitors, their mechanism of action, safety and efficacy as well as its current status among anti-diabetic agents.